2020
DOI: 10.1016/j.trip.2020.100187
|View full text |Cite
|
Sign up to set email alerts
|

Implication of repatriating migrant workers on COVID-19 spread and transportation requirements

Abstract: Nationwide lockdown for COVID-19 created an urgent demand for public transportation among migrant workers stranded at different parts of India to return to their native places. Arranging transportation could spike the number of COVID-19 infected cases. Hence, this paper investigates the potential surge in confirmed and active cases of COVID-19 infection and assesses the train and bus fleet size required for the repatriating migrant workers. The expected to repatriate migrant worker population was obtained by f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
36
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(36 citation statements)
references
References 18 publications
(17 reference statements)
0
36
0
Order By: Relevance
“…Socioeconomic and household factors including motor vehicle or motorcycle ownership as well as the presence of virtual services such as e-commerce, home delivery, ridesharing and other technological factors affect behavior in Jakarta as in wealthier countries ( Irawan et al, 2020 ). In countries such as India, government-imposed lockdowns created urgent need to transport stranded migrant workers back to hometown locations ( Maji et al, 2020 ). Accounting for the surge in cases using a modified susceptible-exposed-infected-removed (SEIR) model, they estimate the train and bus fleet requirements to repatriate migrant workers.…”
Section: Concerns From the Global Southmentioning
confidence: 99%
“…Socioeconomic and household factors including motor vehicle or motorcycle ownership as well as the presence of virtual services such as e-commerce, home delivery, ridesharing and other technological factors affect behavior in Jakarta as in wealthier countries ( Irawan et al, 2020 ). In countries such as India, government-imposed lockdowns created urgent need to transport stranded migrant workers back to hometown locations ( Maji et al, 2020 ). Accounting for the surge in cases using a modified susceptible-exposed-infected-removed (SEIR) model, they estimate the train and bus fleet requirements to repatriate migrant workers.…”
Section: Concerns From the Global Southmentioning
confidence: 99%
“…Based on an observational study of several selected transportation stations in the Greater Accra region of Ghana between March 27 and 29, 2020, Bonful et al (2020) found that many people did not follow COVID-19 prevention measures (social distancing, handwashing) and argued that transport operators need support and guidance to enforce prevention measures. By building a modified susceptible-exposed-infected-removed (SEIR) model, Maji et al (2020) estimated the train and bus fleet sizes required for transporting the repatriating migrant workers in several selected states with high outflux of migrants in India. They found that reducing the flow of migrant workers can help to lower the surge in confirmed and active infection cases.…”
Section: Literature Review Of Research On Covid-19 Policymakingmentioning
confidence: 99%
“…International migrants are commonly employed in construction, agriculture, hospitality, cleaning, transportation, healthcare and personal care sectors (Philippine Statistics Authority 2018 ; Maji et al 2020 ; Ruhs and Anderson 2010 ). Worldwide studies of migration have shown that the male migrant workers are employed in agriculture, construction, the food sector, transport and material moving occupations, while the majority of migrant women workers are employed in the service sectors, such as domestic work, cleaning, catering, hospitality, and the healthcare and manufacturing sectors (Foley and Piper 2020 ; González and Irastorza 2007 ; U.S. Bureau of Labor Statistics 2019 ).…”
Section: Characteristics Of International Migrants’ Workmentioning
confidence: 99%
“…Migrant workers have been studied during the COVID-19 pandemic; they are concentrated in high-risk people-facing industries; hence, there is an inequality in workers’ risk of contracting COVID-19 (Maji et al 2020 ). During the first wave of COVID-19, health care professionals and transportation workers were found to be at the highest risk in many countries.…”
Section: Occupational Health Outcomes For Migrant Workersmentioning
confidence: 99%